Does Bowel Preparation for Colonoscopy Affect Cognitive Function?. Issue 44 (November 2015) - Wadsworth, P.; Blackburne, H.; Dixon, L.; Dobbs, B.; Eglinton, T.; Ing, A.; Mulder, R.; Porter, R.J.; Wakeman, C.; Frizelle, F.A.
Abstract : Abstract: Colonoscopy is a common procedure used in the diagnosis and treatment of a range of bowel disorders. Prior preparation involving potent laxatives is a necessary stage to ensure adequate visualization of the bowel wall. It is known that the sedatives given to most patients during the colonoscopy cause a temporary impairment in cognitive function; however, the potential for bowel preparation to affect cognitive function has not previously been investigated. To assess the effect of bowel preparation for colonoscopy on cognitive function. This was a prospective, nonrandomized controlled study of cognitive function in patients who had bowel preparation for colonoscopy compared with those having gastroscopy and therefore no bowel preparation. Cognitive function was assessed using the Modified Mini Mental State Examination (MMMSE) and selected tests from the Cambridge Neuropsychological Test Automated Battery. Individual test scores and changes between initial and subsequent tests were compared between the groups. Age, gender, and weight were also compared. Forty-three colonoscopy and 25 gastroscopy patients were recruited. The 2 groups were similar for age and gender; however, patients having gastroscopy were heavier. MMMSE scores for colonoscopy and gastroscopy groups, respectively, were 28.6 and 29.5 ( P = 0.24) at baseline, 28.7 and 29.8 ( P = 0.32) at test 2, 28.1 and 28.5 ( P = 0.76) at test 3. Motor screening scores for colonoscopy and gastroscopy groups, respectively, were 349.3 and 354.1 ( P = 0.97) at baseline, 307.5 and 199.7 ( P = 0.06) at test 2, 212.0 and 183.2 ( P = 0.33) at test 3. Spatial working memory scores for colonoscopy and gastroscopy groups, respectively, were 14.4 and 6.7 ( P = 0.29) at baseline, 9.7 and 4.3 ( P = 0.27) at test 2, 10 and 4.5 ( P = 0.33) at test 3. Digit Symbol Substitution Test scores for colonoscopy and gastroscopy groups, respectively, were 36.3 and 37.8 ( P = 0.84) at baseline, 36.4 and 40.0 ( P = 0.59) at test 2, 38.6 and 40.8 ( P = 0.76) at test 3. This study did not find evidence of cognitive impairment resulting from administration of bowel preparation before colonoscopy.